Role and safety of prokinetic drugs in the treatment of upper gastrointestinal motility disorders: an Indian perspective - Chaudhuri, Sujit (International Journal of Research in Medical Sciences, 2023)
Upper gastrointestinal (GI) motility disorders such as functional dyspepsia (FD), gastroesophageal reflux disease, and gastroparesis are associated with symptoms such as acid reflux, regurgitation, bloating, and heartburn. This review summarizes the prevalence, diagnosis and management of upper GI motility disorders in clinical practice in India, with focus on the use of prokinetics. Lifestyle and dietary modifications, psychotherapy, and pharmacotherapy form the armamentarium for management of motility disorders. Among pharmacotherapies, prokinetics increase gastric emptying and provide symptomatic relief. However, neurological and cardiovascular safety issues are associated with commonly prescribed prokinetics making it important to judiciously select an appropriate drug after weighing out its risk-benefit profile. While metoclopramide, domperidone, and levosulpiride are widely prescribed prokinetics in Indian clinical practice, they are associated with adverse effects such as extrapyramidal symptoms (EPS) and cardiovascular side effects. Itopride, which is a prokinetic with dual mechanism of action, has been found to have equivalent efficacy to other prokinetics and has shown significant improvement in quality of life and symptoms in randomized controlled trials in patients with FD. It acts as a D2 receptor antagonist and acetylcholinesterase inhibitor. Both these actions cause increase in acetylcholine levels, which increases gastric motility. Itopride also has negligible cardiac and neurological safety concerns. Thus, it is a relatively safer molecule compared with other prokinetics, with no EPS or cardiotoxicity concerns and can be used for the long-term management of upper GI motility disorders in a wide pool of patient groups either alone or in combination with other drug classes.